MEMBANGUN ZONA INTEGRITAS SEBAGAI UPAYA PEMBERANTASAN KORUPSI - Rizky Aji Shiddiqy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this studi is to explore how is the eforts of Malang City Goverment in building a Zone of Integrity according to Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi No.60 Tahun 2012.This study is conducted with qualitative-desciptive approach, specifically using case study. The data collection was performed through a combination of inteveiw and observation toward the site of research in Malang City Goverment. This study found that Malang City Goverment has implemented 15 from total 19 programs that must be implemented to build Zone of Integrity. Obstacle for those programs are unoccupied of human resources, no alocation from local budget, and there are some arrangement and problems from local goverment that have more priority to be done first. Thus, Unit Penggerak Integritas (UPI) Malang City Goverment must evaluate those programs and soon arrange programs that have not been implemented to creat the wholeness Zone of Integrity in effort to eradicate corruption. Key word : corruption, eradication corruption, Zone of Integirty, National Integrity System